From Curriculum Reform to Classroom Readiness: Elementary Teachers’ Perspectives on Deep Learning in Indonesia’s Merdeka Curriculum - Ana Maghfiroh; Bambang Harmanto; Diyah Atiek Mustikawati; Lathifah; Hesti Rokhaniyah (VELES Voices of English Language Education Society, 2026)
The integration of deep learning into Indonesia’s Merdeka Curriculum reflects a broader shift from curriculum reform to classroom readiness, requiring teachers to translate policy aspirations into meaningful instructional practice. However, this transition depends not only on teachers’ acceptance of reform but also on their conceptual understanding, pedagogical readiness, and access to institutional support. This study explores elementary school teachers’ perspectives on curriculum reform, their understanding of deep learning, and their readiness to implement deep learning-oriented instruction within the Merdeka Curriculum. Using a qualitative exploratory design supported by descriptive questionnaire data, the study involved 18 elementary school teachers and one school principal. Data were collected through questionnaires and semi-structured interviews and analysed using descriptive statistics and thematic analysis. The findings show that most teachers perceived curriculum reform positively because it promotes flexibility, student-centred learning, character development, and twenty-first-century competencies. Teachers also demonstrated a relatively strong understanding of deep learning, associating it with higher-order thinking, real-world application, student engagement, and meaningful learning experiences. However, their readiness remained conditional, given unclear technical guidance, challenges in lesson planning and assessment design, administrative workload, limited resources, and the need for practical professional development. The findings suggest that deep learning-oriented reform cannot be realised through policy change alone. Its classroom implementation requires stronger alignment among curriculum expectations, teacher capacity building, school leadership, instructional resources, and reduced administrative burdens. This study contributes to curriculum reform discourse by highlighting how teacher readiness mediates the translation of deep learning policy into classroom practice in Indonesian elementary education.